The kind worth saving : a novel - Swanson, Peter, 1968- (William Morrow, an imprint of HarperCollinsPublishers, 2023)
"When a private eye starts to follow a possibly adulterous husband, little does he know that the twisted trail will lead back to the woman who hired him--in this spectacularly devious new novel by Peter Swanson featuring characters from his acclaimed novel The Kind Worth Killing"--